The Effect of Religious Values-Based Multiculty Learning on Elementary School Students' Bullying Behavior - Fitriyah, Lailatul; Amrullah, Muhlasin; Rezania, Vanda (Jurnal Kiprah Pendidikan, 2025)
This study aims to determine the effect of multicultural learning based on religious values on bullying behavior of students in elementary schools. The method used is quantitative with a true experimental design with a pretest-posttest control group model. The subjects of the study were third-grade students of Purwodadi 2 Public Elementary School who were divided into experimental and control groups. Data collection was carried out through tests, observations, interviews, and documentation. The results of the analysis using the independent sample t-test showed a significance value of 0.004 (p < 0.05), which indicates a significant difference between the experimental and control groups. Multicultural learning that integrates religious values such as tolerance, compassion, and mutual respect has been proven to be able to reduce bullying behavior significantly. These findings indicate that a learning approach based on religious values not only impacts cognitive aspects but is also effective in shaping the character of students who are tolerant and moral. Thus, this strategy can be used as an alternative in creating a safe, inclusive school environment and supporting holistic character development.